2019
DOI: 10.1029/2018wr024395
|View full text |Cite
|
Sign up to set email alerts
|

Possible Increases in Flood Frequency Due to the Loss of Eastern Hemlock in the Northeastern United States: Observational Insights and Predicted Impacts

Abstract: Trees exert a fundamental control on the hydrologic cycle, yet previous research is unclear about the nuanced relationship between forest cover and riverine flood frequency. In the Northeastern United States, warming air temperatures have resulted in a decline of Eastern Hemlock (EH), and subsequent increases in observed catchment water yield. We evaluated the possibility of EH loss leading to a changed flooding regime. We first investigated plant hydraulic regulation by root water uptake in EH and American Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 105 publications
(187 reference statements)
6
40
0
Order By: Relevance
“…RWU depth variations have been explained by elevation (Martin et al, ), shallow soil water limitation (Meinzer et al, ), and competition with nearby species (Andrews et al, ; Volkmann et al, ). Knighton, Conneely, et al () found deep RWU by Tsuga canadensis was not well explained by topographic position, shallow soil water availability, or nearby competitors for subsurface waters. Our RWU depth estimates (Figures h and j) provided corroborating evidence of plant RWU depths to those reviewed by Evaristo and McDonnell () through independent, temporally continuous measurements collected across larger spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RWU depth variations have been explained by elevation (Martin et al, ), shallow soil water limitation (Meinzer et al, ), and competition with nearby species (Andrews et al, ; Volkmann et al, ). Knighton, Conneely, et al () found deep RWU by Tsuga canadensis was not well explained by topographic position, shallow soil water availability, or nearby competitors for subsurface waters. Our RWU depth estimates (Figures h and j) provided corroborating evidence of plant RWU depths to those reviewed by Evaristo and McDonnell () through independent, temporally continuous measurements collected across larger spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding forest‐scale RWU strategies is critical for developing a process understanding of hydrologic responses to forest cover change. While individual‐ and stand‐level estimates of RWU strategies facilitated by stable isotopes in water and sap flux have become ubiquitous (e.g., Brinkmann et al, ; De Deurwaerder et al, ; Evaristo et al, ; Knighton, Conneely, et al, ), uncertainties in field methods and “scaling‐up” these findings to the catchment remain intractable problems (e.g., Oerter & Bowen, ; Penna et al, ). The metaanalysis of Evaristo and McDonnell () reviewed 531 studies of tree RWU derived from isotopes in water, of which 354 (~67%) used less than 10 xylem samples, possibly missing infrequent locations or periods of deep RWU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catchment tree cover is composed primarily of second‐generation regrowth (stand age approximately 60 years) deciduous American beech (beech) and coniferous eastern hemlock (hemlock; Figure ), though other deciduous species exist at lower densities (Knighton, Coneelly, & Walter, ). Within the mixed hemlock/beech region, hemlock and beech densities are 0.031 and 0.012 m −2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Time lags between δ GP and δ XYLEM have been observed across catchments with varied geologies and climates (e.g., Allen, Kirchner, Braun, Siegwolf, & Goldsmith, ; Knighton, Coneelly, & Walter, ; Brinkmann et al, ), which each study attributed to the residence time within catchment soils prior to RWU. These studies incorporated the open assumption that δ XYLEM reflects the composition of δ RWU as a reasonable approximation at the catchment‐scale during the growing season.…”
Section: Introductionmentioning
confidence: 98%